2015
DOI: 10.1111/tpj.12767
|View full text |Cite
|
Sign up to set email alerts
|

LATERAL ORGAN BOUNDARIES DOMAIN (LBD)10 interacts with SIDECAR POLLEN/LBD27 to control pollen development in Arabidopsis

Abstract: SUMMARYDuring male gametophyte development in Arabidopsis thaliana, the microspores undergo an asymmetric division to produce a vegetative cell and a generative cell, which undergoes a second division to give rise to two sperm cells. SIDECAR POLLEN/LATERAL ORGAN BOUNDARIES DOMAIN (LBD) 27 plays a key role in the asymmetric division of microspores. Here we provide molecular genetic evidence that a combinatorial role of LBD10 with LBD27 is crucial for male gametophyte development in Arabidopsis. Expression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 57 publications
(72 reference statements)
1
49
0
Order By: Relevance
“…SCP is a microspore-specific LATERAL ORGAN BOUNDARIES-DOMAIN/ASYMMETRIC LEAVES2-LIKE (LBD/ASL) domain family protein, whose expression overlaps with that of other family members in developing pollen. SCP (LBD27) and LBD10 form nuclear-localised heterodimers and act synergistically to control pollen development (Kim et al, 2015). Thus, combinatorial interactions among LBD proteins are thought to be important for their roles in the male gametophyte (Kim et al, 2016).…”
mentioning
confidence: 99%
“…SCP is a microspore-specific LATERAL ORGAN BOUNDARIES-DOMAIN/ASYMMETRIC LEAVES2-LIKE (LBD/ASL) domain family protein, whose expression overlaps with that of other family members in developing pollen. SCP (LBD27) and LBD10 form nuclear-localised heterodimers and act synergistically to control pollen development (Kim et al, 2015). Thus, combinatorial interactions among LBD proteins are thought to be important for their roles in the male gametophyte (Kim et al, 2016).…”
mentioning
confidence: 99%
“…15 Analysis of mature pollen grains and developmental analysis indicated that LBD10 is involved in microspore polarization prior to the first asymmetric division and also in germ cell mitosis. These results indicated that LBD10 plays an overlapping role with LBD27 during PMI, but also plays a distinct role during PMII.…”
mentioning
confidence: 99%
“…Recent studies have expanded their functional diversity beyond the definition of lateral organ boundaries. The LBD family proteins also play pivotal roles in pollen development (9,10), vascular differentiation (11), nitrogen metabolism (12), plant regeneration (13,14), photomorphogenesis (15), disease susceptibility (16,17), and some specific developmental processes in wood and grass species (18,19).…”
Section: Lateral Organ Boundaries Domain (Lbd) Proteins a Family Of mentioning
confidence: 99%
“…Homo-and heterodimerization are generally observed within LBD proteins (10,50). However, it was not clear whether LBD proteins function as monomers in cells.…”
Section: Crystal Structure Of a Lob Domain Proteinmentioning
confidence: 99%